The effectiveness of nursing in intermediate care related to an integrated concept of dependency: a case study using the Modified Barthel index - Sara Falchi; Silvio Quirini; Nikita Valentina Ugenti; Yari Longobucco; Sandra Scalorbi (Infermieristica Journal, 2024)
Introduction. A new care setting was established In modern society, called intermediate care (IC). It refers to residential structures aimed at link hospital and patient’s home, ensuring improved and personalized continuity of care and achieve better health outcomes. Patients admitted in this setting are usually elderly, with high levels of dependency. One of the most used assessment tools for dependency is Barthel Index (BI) and its modified version: the Modified Barthel Index (MBI). The aim of this paper is to verify if care in community hospital (intermediate care) improves patient independence (measured with Modified Barthel Index), and this improvement is linked to an appropriate care model.